Superalloys 718, 625, 706 and Various Derivatives (2001) 2001
DOI: 10.7449/2001/superalloys_2001_691_700
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Considerations of Oxygen Enhanced Crack Growth in INCONEL 718

Abstract: A coordinated, multidisciplinary study was conducted to elucidate the mechanism for oxygen enhanced crack growth in Inconel 718 at high temperatures. Sustained-load tests were conducted in high-purity argon and oxygen, at 873 to 973 K, to characterize the kinetics of crack growth. The reactivity of the alloy, Nb, NbC and Ni3Nb with oxygen was determined by x-ray photoelectron spectroscopy (XPS). Crack growth experiments, in oxygen at 973 K, were interrupted and the specimens were charged with hydrogen and frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Refs 52, 55 and 56. Wei et al 57 and Miller et al 58,59 found an enrichment of the bct c0 phase (Ni 3 Nb) at the grain boundaries and concluded that the formation of a thin intergranular Nb 2 O 5 film cracks in a brittle manner, leading to high crack propagation rates (Fig. 8a).…”
Section: Time-dependent Intergranular Failure Of Ni-base Superalloysmentioning
confidence: 98%
“…Refs 52, 55 and 56. Wei et al 57 and Miller et al 58,59 found an enrichment of the bct c0 phase (Ni 3 Nb) at the grain boundaries and concluded that the formation of a thin intergranular Nb 2 O 5 film cracks in a brittle manner, leading to high crack propagation rates (Fig. 8a).…”
Section: Time-dependent Intergranular Failure Of Ni-base Superalloysmentioning
confidence: 98%